OHP-025 Investigations following increasing complaints about infusion sets for safe administration of cytostatics. (24th March 2015) - Peyrilles, E; Fremont, D; Le Guyader, G; Perrinet, M; Storme, T; Massot, V
Abstract : Background: Systematic use of flushed infusion lines is recommended by the French "Good Compounding Practices" for the administration of chemotherapy drugs. When they are packaged in syringes, the CytoBolus Adapter Set (CODAN) is currently used in a department of paediatric haematology. Since September 2013, 27 adverse events have been reported, including 20 occlusions and 6 leaks of this device. Viscosity has been cited by the manufacturer as a possible causal factor. Purpose: The purpose of this study was to identify risk factors that lead to CytoBolus Adapter Setmalfunction, especially viscosity. Material and methods: An Ishikawa diagram was built after meeting with nurses, pharmacists and CODAN representatives. Three connectors were assessed: the CytoBolus Adapter Set, the PhaSeal system and a plain tube (VYGON). In vitro, three solutions with an increasing viscosity were processed by 4 automated Orchestra infusion systems at two extreme flow rates: 1 ml/h for 20 h and 50 ml/h for 1 h. Each combined setting was repeated 3 times. A two-way ANOVA test was used to compare means of calculated volumes, based on the density of each solution. Results: Cause and effects analysis identified potential causes of the events including cold storage, properties of the solvent, misuse and mishandling, or the lack of resistance of the connector. No significant differences were observed in the volume delivered by the three medical devices at 50 ml/h whatever the viscosity. Volumes delivered by the PhaSeal system were unexpectedly lower with water for injection than dextrose 5% (p = 0.00405) and dextrose 10% (p = 0.00334) at 1 ml/h but were still acceptable given the 3% precision of the Orchestra (standard NF S 90–251). In all the 216 experiments, neither obstruction nor cracking was observed. Conclusion: The viscosity does not appear to be the determining factor that leads to malfunction. Further investigations appear necessary of other causal factors. References and/or acknowledgements: Pharmacy Department, Robert Debré Hospital. No conflict of interest.